Diálogo creativo : hablar para pensar en el aula - Fisher, Robert, 1943- (Ediciones Morata, 2013)
'Creative Dialogue' is an essential guide to dialogic learning, presenting practical ways of teaching children to be more thoughtful and creative and to learn more effectively through speaking and listening in school and at home.